A NEW SPECIMEN OF MACROPLACUS RAETICUS SCHUBERT-KLEMPNAUER, 1975 (SAUROPTERYGIA, PLACODONTIA) FROM THE UPPER TRIASSIC OF ITALY, WITH REMARKS ON PLACODONT PHYLOGENY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
A new placodont specimen—an incomplete, three-dimensionally preserved skull encased in a carbonate matrix—is described here. Although discovered in slope debris, strong evidence suggests that the fossil most likely originated from the Rhaetian (Upper Triassic) Zu Limestone. Anatomical study—including X-ray computed tomography (CT)—comparison with other placodont species, and phylogenetic analysis support attribution of the new specimen to the cyamodontoid placodont Macroplacus raeticus Schubert-Klempnauer, 1975. Until now, this species was known solely from its holotype: a skull from the Rhaetian of the Bavarian Alps, which we have re-examined and, in part, reinterpreted. The new specimen shows the closest morphological affinity to the Macroplacus holotype among all known placodonts; the significant size difference between the two is explained as representing different ontogenetic stages of the same taxon. Our species-level phylogenetic analysis of Placodontia supports a sister-taxon relationship between the new specimen and Macroplacus. The analysis builds upon previous studies, incorporating revised descriptions and updated character coding for a substantial number of skull traits, the addition of new characters and taxa, and overall improvements to the phylogenetic dataset for current and future analyses. Macroplacus raeticus remains the only placodont species known exclusively from the Rhaetian. Along with the morphologically similar Psephoderma alpinum—from the Norian and Rhaetian—it represents the latest occurrence of placodonts in the Upper Triassic, strengthening the case for a close evolutionary relationship between these two taxa.
Keywords: Zu Limestone; Orobic Alps; Cyamodontoidea; skull; dentition; character description and coding.